Costs of Formal and Informal Home Care and Quality of Life for Patients with Multiple Sclerosis in Sweden. (4th March 2014) - Svensson, Marianne; Fajutrao, Liberty
Abstract : Disease progression in multiple sclerosis leads to dramatic changes in a person's ability to perform daily activities and increases reliance on external help. This study aims to describe and to estimate costs of formal/informal home care and quality of life related to multiple sclerosis. A mailed survey to a random sample of MS sufferers ( n = 1500 ) collected data on the number of hours of home care received, type of help, productivity losses, quality of life, and disease characteristics. Costs for home care were estimated in 2012 € and factors that may influence the likelihood of getting home care were also evaluated. Formal care was given to 27% of the respondents ( n = 839 ) at an average of 238.7 hrs/month at a mean monthly cost of €2873/person with MS. Informal care was received by 49% of the respondents at an average of 47.3 hrs/month at a mean monthly cost of €389/person with MS. Utilities across disease severity are as follows: mild MS = 0.709 (sd = 0.233), moderate MS = 0.562 (sd = 0.232), and severe MS = 0.284 (sd = 0.283). Total home care costs increased with increasing disease severity. Informal caregiving contributes significantly to MS home care in Sweden.